Simulation, modelling and packet sniffing facilities for IoT: A systematic analysis - Bimal Patel; Parth Shah (Institute of Advanced Engineering and Science, 2020)
Man and Machine in terms of heterogeneous devices and sensors collaborate giving birth to the Internet of Things, Internet of future. Within a short span of time 30billions intelligent devices in form of smart applications will get connected making it difficult to test and debug in terms of time and cost.Simulators play vital role in verifying application and providing security before actually deploying it in real environment.Due to constraint environment in terms of memory, computation, and energy this review paper under a single umbrella will throw insight on comprehensive and in-depth analysis keeping in mind various barriers, critical design characteristics along with the comparison of candidate simulator and packet sniffing tool. Post simulated analysis play vital role in deciding behavior of data and helping research community to satisfy quality of service parameters.This review makes it feasible to make an appropriate choice for simulators and network analyzer tool easy fulfilling needs and making IoT a reality